syofiah ANALISIS PEMANFAATAN MEDIA SOSIAL SEBAGAI STRATEGI PROMOSI DAN PEMASARAN DALAM BERWIRAUSAHA: ANALISIS PEMANFAATAN MEDIA SOSIAL SEBAGAI STRATEGI PROMOSI DAN PEMASARAN DALAM BERWIRAUSAHA - syofiah (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2022)
Home business is one type of micro and small business (MSME) which is seen from its economic scale which is still low but is able to become one of the important parts in the economy of a country with the number of home businesses currently very large and dominant. The purpose of this study was to find out and analyze the use of social media as a promotion and marketing strategy by the "Novi Sari" bouquet home business located on Jl. Surapati lk. Lll Ps. Sibuhuan. This scientific article focuses on the Promotion and Distribution strategies employed by this home business. Based on the results of observations, it can be said that there are several stages that affect the success of promotion and marketing strategies through social media, namely (1)Creating a special account (2)Utilizing all social media features (3)Daily updates (4)Product descriptions (5)Utilizing hashtags from buyers (6)Fast and friendly service (7)Make discounts or discounts (8)Give bonuses for every purchase (9)Make honest ads (10)On testimonials from customers.